GEOMECHANICS STUDI FOR COAL BED METHANE RESERVOIR USING NUMERICAL AND PHYSICAL MODELLING - NURHIDAYAT (NIM : 10209057), GALIH
Geomechanics studi is important to understand how make stable state condition in wellbore. After we design stable state at wellbore, we can run the production activity effectively and efficiently. There are two kind of stress, vertical stress and horizontal stress. In general vertical stress called overburden stress. Otherwise, horizontal stress called tektonic stress. Failure at horizontal wellbore happened at the higher stress of the wellbore. Crack generate at the east side and of west side of wellbore because they have minimum stress distribution rather than east and west side of stress distribution around wellbore. For coal strength measurement, cleat distribution effect the strength character of coal. For modulus young from sample A, the value is 0.2 GPa. And for sample B modulus young value reaching 0.4 GPa.